Female breast cancers are getting smaller, but socio‐demographic differences remain - Colin Luke; Ann‐Minn Nguyen; Kevin Priest; David Roder (Elsevier, 2004)
Abstract Objective:To investigate trends towards early detection of infiltrating ductal carcinomas, possible effects on patients' prognosis, and characteristics of women still at high risk of late detection. Methods:South Australian Cancer Registry data were analysed to compare breast tumour diameters for the 1980-86 and 1997-2002 diagnostic periods by age. Relative survivals for 1980-86 were compared with corresponding survival estimates for 1997-2000, obtained by weighting diameter‐specific survivals for 1980-86 to equate with the diameter distribution for 1997-2002. Multivariable logistic regression was used to determine socio‐demographic predictors of large diameters (≤30 mm) in 1997-2002. Results:The proportion of tumours with diameters smaller than 15 mm increased from 13.0% in 1980-86 to 36.7% in 1997-2002, whereas the proportion with large diameters reduced from 43.0% to 18.6%. Estimated changes in 20‐year survivals equated with a 33% reduction in breast‐cancer mortality among patients aged 50-69 years at diagnosis. Data for 1997-2002 indicate that early diagnosis is not evenly distributed, with large diameters more common in age ranges outside the 50-69 year target for mammography screening; low socio‐economic areas; non‐Caucasians; patients born in northern/eastern Europe and potentially Asia/Middle East; and in some country locations. Conclusions and implications:Increased emphasis on early detection should be directed at sectors of the population where delays in diagnosis and poorer prognosis are evident. Projected reductions in breast‐cancer mortality among patients are indicative of effects of earlier detection on patients' prognosis, but require confirmation with follow‐up data. More particularly, parallel studies of effects on population‐based mortality are warranted.